Sources of human non-typhoid salmonellosis: A review - de Freitas Neto, O. C. [UNESP]; Penha Filho, R. A.C. [UNESP]; Barrow, P.; Berchieri, Jr. [UNESP] (My University, 2010)
Salmonellosis is a worldwide disease caused by bacteria of the genus Salmonella. Currently, there are over 2,500 identified serovars of Salmonella. A reduced number of these serovars, about eighty, are implicated in most animals and human diseases. Most cases of salmonellosis in humans are associated with the consumption of contaminated food products such as beef, pork, poultry meat, eggs, vegetables, juices and other kind of foods. It may also be associated with the contact between humans and infected pet animals. Therefore, the chain of human salmonellosis is very complex and in most cases the origin of the infection is difficult to establish. The use of antimicrobial agents to treat and to prevent bacterial infections in humans and animals, as well as as growth promoters in animal production, has favoured the selection and transference of resistance genes between different bacteria, including Salmonella serovars. Many studies have confirmed the role of foods of animal origin as a source of multi drugresistant Salmonella serovars. For this reason, continuous surveillance of these pathogens along the food chain together with the responsible use of antimicrobial agents is necessary.
Keywords: Antimicrobial resistance; Beef; Food; Pork; Poultry; Salmonella spp.; Vegetables